Pengembangan Sistem Kasir Berbasis Digital Untuk Mempermudah Transaksi Penjualan di Warung - Ninik Rahayu Ashadi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The objectives of this study are (1) to know how to design the development of a digital-based cashier System to facilitate in-store sales transactions, (2) to know how the user feasibility towards the users of a digital-based cashier system. This type of research is a quantitative type of research, This research uses Research and Development (RD) approach using Prototype development model. the results of the study are (1) A digital based cashier system to facilitate sales transactions in this stall was designed using the Prototype Model development model, (2) The percentage results will be converted in categories. Based on the percentage result obtained a score of 83.75 % then it belongs in the category of â€œvery easy to use / very feasibleâ€ . so that it can be concluded that (1) A digital-based cashier system to facilitate sales transactions in this stall was designed using the Prototype Model development model. This development model includes: (a) Requirement Gathering, (b) Quick Design, (c) Prototype Building, (d) User Evaluation and Feedback. as high as 83.75 % if converted in the category is on â€œvery easy to use / very feasibleâ€ so that the feasibility of users towards users of digital based cashier system is feasible and easy to use.